(untitled) - Feder, Stuart (Cambridge, 1999)
Ives' life (1874-1955) spanned two centuries; he grew up in the nineteenth and composed chiefly in the twentieth. His nostalgia for a simpler life in the New England town of his youth is revealed in his frequent musical quotation of songs of that earlier time: parlor and patriotic songs, hymns and gospel music that he learned from his father, a village bandmaster, and the most important influence on his life and music. This book clarifies the complexity of the man and his music--music that is uniquely autobiographical and that itself illuminates the narrative.
Keywords: Composers,Người soạn nhạc; United States,Hoa Kỳ